A internet como recurso no processo de escritura de um artigo de opinião - Gotz, Giseli (2020)
This work seeks to analyze which the possible impactscaused on the production of a text, specifically on the opinion article genre, from the free use of the internet. Thus, the general objective is guided by analyzing, whichare the influences of the internet on the writing of an opinion article and how these influences affectsthe resultof the text. This general objective is unfolded in other specific objectives, which seek, essentially, to comprehend in which situations the students use the internet to the writing of an opinion article; to verify if this search on the internet is or is not determinant to the final result of the text, and; to identify if there was criticality in the moment of selecting the relevant information to the writing of the genre.Therefore, so that it is possible to find answers to our questions, this research presents theoretical foundation on Mikhail Bakhtin (1997), related to discourse genres;Severiano et al.(2019) about the compositional characteristics of the opinion article genre; Coscarelli (2016) on the acts of reading and browsing; Lawless and Schrader (2008) regarding behavioral and cognitive skills; Wiley et al.(2009) for navigation standards; and David Barton and Carmen Lee (2015) approaching texts and digital practices. The data collection happened on the "Workshop of Reading, Writing and Rewriting of Opinion Articles", registered as an extension project at the Federal University of Technology -Paraná State, Brazil, Pato Branco campus, and had the participation of High School students. Altogether, 05 texts wereanalyzed from two articulists that took part in all the classes. So that the analyzes were possible, the ScreenHunter software was used, bearing in mind that from this it is possible to view all the movements of the computer screen at the time of the writing of the text. Thus, the analysis of the five texts allows us to infer that an internet was applied in the elaboration of practically all stages of the texts, from the choice of the theme, to the writing of the conclusion. Reading and navigation skills were affected by actions related to a literal copy of information, from ready-made essays found on websites, without analyzingthe content conveyed. In addition, it is noticeable that the writer has mastery of the digital medium, to move between the sites and navigate between the links, he uses this information superficially in some moments, which is necessary to control behavioral skills, but impasses in skills cognitive, conceptualized Lawless and Schrader (2008). Thinking about the navigation patterns proposed byWiley (2009), we consider that the use of reliable sites has progressed with each text, however, the last scripture did not follow this pattern, since the bank of model newsrooms constituted an obstacle to navigation. The information contained in these pages was easier to find and, sometimes, in this last text, the columnist opted for copying the contents (from untrusted sites), which also compromised the navigation process.Therefore, this research reveals that it is also the role of the current teacher to instruct how to read, navigate and how to select reliable information, guiding the critical analysis of this information based on cognitive strategies that enable inferences, interpretations and evaluations to be carried out.